Regulation of cardiac hypertrophic signaling by prolyl isomerase Pin1 - Toko, Haruhiro; Konstandin, Mathias H.; Doroudgar, Shirin; Ormachea, Lucia; Joyo, Eri; Joyo, Anya Y.; Din, Shabana; Gude, Natalie A.; Collins, Brett; Völkers, Mirko; Thuerauf, Donna J.; Glembotski, Christopher C.; et al. (Circulation research, 2013)
Rationale: Cardiac hypertrophy results from the complex interplay of differentially regulated cascades based on the phosphorylation status of involved signaling molecules. Although numerous critical regulatory kinases and phosphatases have been identified in the myocardium, the intracellular mechanism for temporal regulation of signaling duration and intensity remains obscure. In the nonmyocyte context, control of folding, activity, and stability of proteins is mediated by the prolyl isomerase Pin1, but the role of Pin1 in the heart is unknown. - Objective: To establish the role of Pin1 in the heart. - Methods and Results: Here, we show that either genetic deletion or cardiac overexpression of Pin1 blunts hypertrophic responses induced by transaortic constriction and consequent cardiac failure in vivo. Mechanistically, we find that Pin1 directly binds to Akt, mitogen activated protein kinase (MEK), and Raf-1 in cultured cardiomyocytes after hypertrophic stimulation. Furthermore, loss of Pin1 leads to diminished hypertrophic signaling of Akt and MEK, whereas overexpression of Pin1 increases Raf-1 phosphorylation on the autoinhibitory site Ser259, leading to reduced MEK activation. - Conclusions:Collectively, these data support a role for Pin1 as a central modulator of the intensity and duration of 2 major hypertrophic signaling pathways, thereby providing a novel target for regulation and control of cardiac hypertrophy.
Gesehen am 10.02.2022